In Vitro and In Situ Activity-Based Labeling of Fibroblast Activation Protein with UAMC1110-Derived Probes - Van Rymenant, Yentl; Tanc, Muhammet; Van Elzen, Roos; Bracke, An; De Wever, Olivier; Augustyns, Koen; Lambeir, Anne-Marie; Kockx, Mark; De Meester, Ingrid; Van Der Veken, Pieter (Frontiers in Chemistry, 2021)
Fibroblast activation protein (FAP) is a proline-selective protease that belongs to the S9 family of serine proteases. It is typically highly expressed in the tumor-microenvironment (TME) and especially in cancer-associated fibroblasts, the main cell components of the tumor stroma. The exact role of its enzymatic activity in the TME remains largely unknown. Hence, tools that enable selective, activity-based visualization of FAP within the TME, can help to unravel FAP’s function. We describe the synthesis, biochemical characterization and application of three different activity-based probes (Biotin, Cy3- and Cy5-labeled) based on the FAP-inhibitor UAMC1110, an in-house developed molecule considered to be the most potent and selective FAP inhibitor available. We demonstrate that the three probes have sub-nanomolar FAP affinity and pronounced selectivity with respect to the related S9 family members. Furthermore, we report that the fluorescent Cy3- and Cy5-labeled probes are capable of selectively detecting FAP in a cellular context, making these chemical probes highly suitable for further biological studies. Moreover, proof of concept is provided for in situ FAP activity staining in patient-derived cryosections of urothelial tumors.